2014
DOI: 10.1103/physreve.90.012107
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium ensemble inequivalence and large deviations of the density in theABCmodel

Abstract: We consider the one-dimensional driven ABC model under particle-conserving and particle-nonconserving processes. Two limiting cases are studied: (a) The rates of the nonconserving processes are vanishingly slow compared with the conserving processes in the thermodynamic limit and (b) the two rates are comparable. For case (a) we provide a detailed analysis of the phase diagram and the large deviations function of the overall density, G(r). The phase diagram of the nonconserving model, derived from G(r), is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…We now consider the constant-pressure version of the model, in which the system size evolves in time according to equation (5). In equilibrium, one expects local properties of single phases to be independent of ensemble.…”
Section: Results -Constant-pressurementioning
confidence: 99%
See 1 more Smart Citation
“…We now consider the constant-pressure version of the model, in which the system size evolves in time according to equation (5). In equilibrium, one expects local properties of single phases to be independent of ensemble.…”
Section: Results -Constant-pressurementioning
confidence: 99%
“…Out-of-equilibrium systems differ from their equilibrium counterparts in many ways. For example, longranged correlations are generic in non-equilibrium steady states [1,2]; unusual phase transitions can take place [3]; and there may be significant differences in behavior for the same system in different ensembles (for example, canonical and grand canonical [4,5]). Recently, there has been considerable interest in large-deviation phenomena [6], based on ensembles of trajectories that are conditioned on atypical values of time-averaged observables [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Anomalous coarsening with logarithmic domain growth has been identified in a variety of situations with dynamical constraints, as for example in the ABC model introduced by Evans et al [26,27], where three different particle types swap places asymmetrically, in the model discussed by Lahiri and Ramaswamy [28,29], where two sublattices are considered with two types of particles on each sublattice, or in the driven two-lane particle system studied by Lipowski and Lipowska [30]. Among these models, the one-dimensional ABC model has enjoyed much attention in recent years [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], due to its unique properties combined with its amenability to exact calculations in some special cases. Thus the ABC model provides an opportunity to study exactly the long-range correlations in a system undergoing a non-equilibrium phase transition as well as to elucidate ensemble inequivalence far from equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…The inequivalence of different ensembles in the Blume-Emery-Griffiths model has been reported earlier in [12,22] in the absence of magnetic field. In the (T − ∆) plane, while the λ line equation is same in both the ensembles, the first order line and the multicritical points are known to be located differently [36][37][38][39]. It was reported that the TCP and other multicritical points are different for canonical and microcanonical ensembles for a given value of K [12,22].…”
Section: Ensemble Inequivalencementioning
confidence: 97%